EFFECTS OF E BANKING ON EMPLOYEE SATISFACTION AMONG STAFF - Sharon Amoding (UGANDA CHRISTIAN UNIVERSITY, 2024)
The purpose of this study was to investigate the Effects of E- banking on Employee Satisfaction among staff in the case study of Uganda Christian University .the study was based on the objectives such as To establish if employees have adequate skills in the use of e- banking , To determine how easy the e-banking is to use , To determine whether availability of the internet influences ease of use of e- banking .the study was conducted from Uganda Christian University main branch and target population was 46 and the sample size was 36 respondents using a methodology of questionnaire to collect data .the study was conclude that the adoption of e- banking has neutral impact on how staff have adequate skills in using e-banking at 27.8% and examine whether staff find it easy to use e-banking 33.33% of the respondents and to examine whether availability internet affects the usage of e- banking was minor impact meaning the staff are find it easy when using it. There were several challenges I faced while carrying out this research based on the study effects of e- banking on employee satisfaction among staff such as the study time frame may not captured and the long-term effects of e- banking on employee satisfaction .the study recommendations were to continuously improve on our e- banking system , to enhance employee satisfaction and get feedback from them .